Enhancing the operationalization of the African Union’s climate change and resilient development Strategy and action Plan (2022-2032) - Chevallier, Romy; Chesterman, Sabrina (African Union, 2022)
On 6 February 2022, the African Union’s Climate Change and Resilient Development Strategy and Action Plan (2022-2032) was endorsed at the 35th Ordinary Session of the African Union (AU’s) Assembly of African Heads of State and Government. This Strategy is Africa’s first collective climate action plan, seeking to harmonise the continent’s response to climate change over the next decade, and setting out the key guiding principles, priorities, and intervention areas for enhanced cooperation. While the adoption of the AU Climate Strategy represents a key step in shaping Africa’s long-term climate change response and presenting a unified voice towards COP27 and beyond, there is an urgent need to translate the commitments and priority areas outlined in this document into tangible and meaningful action. For the Strategy to succeed, immediate actions are needed to maintain momentum and enhance its operationalisation. In this regard, the African Union Commission invited experts to a meeting to discuss the key elements and activities needed for the operationalisation of the Strategy. This includes the planning of specific mechanisms to enhance the Strategy’s broad-based ownership and increase programmatic synergies and alignment, as well as actions to promote its political prioritisation, sensitisation and dissemination, partnership development, resource mobilisation, and support transparency and accountability.